ANALISIS FAKTOR-FAKTOR YANG MEMPENGARUHI HARGA SAHAM PT.TELKOM TBK DI BURSA EFEK JAKARTA - Mihrani Mihrani (Jurnal Bisnis dan Kewirausahaan, 2015)
The objective is to determine the ROE and EVA pengruh on stock prices PT.Telkom.Tbk in the Jakarta Stock Exchange. While the benefits of writing as material information to investors, potential investors or parties interested in taking a decision before making an investment, and as an experience and lesson for writers in applying theories obtained, in particular those relating to the object of this paper. Based on the multiple regression models that have been found above, if the impairment ROE Rp 1, - it will increase the share price of 25.368, while the variable conditions EVA shows no function at all because the variable regression coefficient indicates at 0. Determinant coefficient calculation results obtained by the simultaneous effect of 40.4%, which means that changes in the price of PT. Telkom Tbk more dominant separation is influenced by other factors, which allowed researchers to mnelitinya further. Simultaneously test results did not show significance so clearly it can be said that both of these variables did not influence. While the partial test results for each variable ROE and EVA also showed no effect, so further clarify the conditions of these variables to changes in stock prices on PT Telkom Tbk